Clinical and pathological characteristics of patients with non-Hodgkin lymphoma cases in Eastern Turkey - Dogan, Ali; Dogan, Narin Yildirim; Erkurt, Mehmet Ali; Ekinci, Omer; Kuku, Irfan; Kaya, Emin (Cukurova Univ, Fac Medicine, 2020)
Purpose: This study aims to evaluate the epidemiological, demographic and clinical characteristics, and prognostic factors of the patients with non-Hodgkin lymphomas (NHL). Materials and Methods: All patients diagnosed with NHL at the Department of Hematology of Inonu University Faculty of Medicine (Turkey) between 2000 and 2016 were evaluated for this study. Only patients older than 18 years were included in the study. Characteristics were evaluated by reviewing patients' records retrospectively. Results: Of the 386 patients studied, 242 (62.7%) were male and 144 (37.3%) were female and the overall median age was 53 years (range: 18-92). The most common histological subtype of NHL was diffuse large B-cell lymphoma (DLBCL) (46.9%). In univariate analyses, advanced stage (III-IV), high-intermediate to high risk category disease based on IPI score, bone marrow involvement at diagnosis, haemoglobin levels below 10 g/dL, increased LDH levels, primary nodal involvement, the presence of B symptoms, the exigency of autologous bone marrow transplant, and not receiving rituximab-based chemotherapy regimens as the primary treatment were all associated with shorter overall survival. Conclusion: The prevalence, clinical characteristics, histopathological subtypes, treatment responses, and overall survival rates may differ because NHL is a heterogeneous disease group and may vary according to a geographical area. Therefore, treatment should be individualized according to disease subtype.
Keywords: Lymphoma; non-hodgkin lymphoma; diffuse large b-cell lymphoma